Predictors of incomplete immunization coverage among one to five years old children in Togo - Dadja Essoya Landoh (BMC Public Health, 2016)
Abstract Background Incompleteness of vaccination coverage among children is a major public health concern because itcontinues to sustain a high prevalence of vaccine-preventable diseases in some countries. In Togo, very few data on the factors associated with incomplete vaccination coverage among children have been published. We determined the prevalence of incomplete immunization coverage in children aged one to five years in Togo and associated factors. Methods This was a cross-sectional study using secondary data from the 2010 Multiple Indicator Cluster Surveys (MICS4) conducted in 2010 among children aged 1 to 5 years in Togo. This survey was conducted over a period of two months from September to November, 2010. Results During Togo’sMICS4 survey, 2067 children met the inclusion criteria for our study. Female children accounted for 50.9 % (1051/2067) of the sample and 1372 (66.4 %) lived in rural areas. The majority of children (92.2 %; 1905/2067) lived with both parents and 30 % of the head of households interviewed were not schooled (620/2067). At the time of the survey, 36.2 % (750/2067) of the children had not received all vaccines recommended by Expanded Program on Immunization (EPI). In multivariate analysis, factors associated with incompleteness of immunization at 1 year were: health region of residences (Maritime aOR = 0.650; p = 0.043; Savanes: aOR = 0.324; p <0.001), non-schooled mother (aOR = 1.725; p = 0.002),standard of living (poor: aOR = 1.668; p = 0.013; medium: aOR = 1.393; p = 0.090) and the following characteristics of the household heads: sex (aOR = 1.465; p = 0.034), marital status (aOR = 1.591; p = 0.032), education level(non-educated: aOR = 1.435; p = 0.027. Conclusion The incomplete immunization coverage among children in Togo remains high. It is necessary to strengthen health promotion among the population in order to improve the use of immunization services that are essential to reduce morbidity and mortality among under five years old children.